Torque and power-velocity relationships in cycling: Relevance to track sprint performance in world-class cyclists - Dorel, S.; Hautier, C. A.; Rambaud, O.; Rouffet, D.; van Praagh, E.; Lacour, J.-R.; Bourdin, M. (International Journal of Sports Medicine, 2005)
The aims of the present study were both to describe anthropometrics and cycling power-velocity characteristics in top-level track sprinters, and to test the hypothesis that these variables would represent interesting predictors of the 200 m track sprint cycling performance. Twelve elite cyclists volunteered to perform a torque-velocity test on a calibrated cycle ergometer, after the measurement of their lean leg volume (LLV) and frontal surface area (Ap), in order to draw torque- and power-velocity relationships, and to evaluate the maximal power (Pmax), and both the optimal pedalling rate (ƒopt) and torque (Topt) at which Pmax is reached. The 200 m performances - i.e. velocity (V200) and pedalling rate (ƒ200) - were measured during international events (REC) and in the 2002 French Track Cycling Championships (NAT). Pmax, ƒopt, and Topt were respectively 1600 ± 116 W, 129.8 ± 4.7 rpm and 118.5 ± 9.8 N · m. Pmax was strongly correlated with Topt (p < 0.001), which was correlated with LLV (p < 0.01). V200 was related to Pmax normalized by Ap (p = 0.05) and also to ƒopt (p < 0.01) for REC and NAT. ƒ200 (155.2 ± 3, REC; 149 ± 4.3, NAT) were significantly higher than ƒopt (p < 0.001). These findings demonstrated that, in this population of world-class track cyclists, the optimization of the ratio between Pmax and Ap represents a key factor of 200 m performance. Concerning the major role also played by ƒopt, it is assumed that, considering high values of ƒ200, sprinters with a high value of optimal pedalling rate (i.e. lower ƒ200 - fopt difference) could be theoretically in better conditions to maximize their power output during the race and hence performance.